Distinguishing Short‐Term Versus Long‐Term Responses in Cover‐Class Structured Community Dynamics: A Test With Grassland Drought Response - Gupta, Aryaman; Gascoigne, Samuel J. L.; Barabás, György; Blonder, Benjamin Wong; Qi, Man; Fenollosa, Erola; Thornley, Rachael; Hernandez, Christina; Hector, Andy; Salguero‐Gómez, Roberto (Ecology letters, 2025)
ABSTRACT Climate change is increasing the magnitude and frequency of precipitation extremes. Consequently, grassland community dynamics are destabilising and becoming harder to predict since models typically simulate long‐term (asymptotic) behaviour, potentially neglecting short‐term (transient) behaviour. Here, we use cover data from an experiment performed over 8 years to model short‐ and long‐term responses of three functional groups (grasses, legumes, and non‐leguminous forbs) to precipitation extremes. We use Integral Projection Models (IPMs) and pseudospectral theory to track transient grassland community dynamics driven by response lags and interannual shifts. We show that the cover‐class structure and inter‐cover‐class interactions of functional groups make them transiently unstable but asymptotically stable, that is, disturbances are initially amplified before eventually dissipating. We also show that grasses dominate under irrigation, while legumes and forbs dominate under drought. We demonstrate that the pseudospectra of IPMs enable computationally and data‐wise inexpensive assessment of whether transient dynamics drive community responses to disturbances. We use Integral Projection Models (IPMs) and pseudospectral theory to track short‐term (transient) dynamics of a grassland subject to experimental precipitation shifts. We show that the cover‐class structure of functional groups makes them transiently unstable but asymptotically stable, that is, disturbances initially amplify before dissipating. The pseudospectra of community matrices from those IPMs enable computationally and data‐light assessment of transient community responses to disturbances.